Small (sendai negative) branch-cuct IPMNs: not harmless - Fritz, Stefan; Klauß, Miriam; Bergmann, Frank; Hackert, Thilo; Hartwig, Werner; Strobel, Oliver; Schwarz-Bundy, Bogáta D.; Büchler, Markus W.; Werner, Jens (Annals of surgery, 2012)
Objective: The aim of this study was to evaluate existing management guidelines for branch-duct intraductal papillary mucinous neoplasms (IPMNs). Background: According to current treatment guidelines (Sendai criteria), patients with asymptomatic branch-duct type IPMNs of the pancreas less than 3 cm in diameter without suspicious features in preoperative imaging should undergo conservative treatment with yearly follow-up examinations. Nevertheless, the risk of harboring malignancy or invasive cancer remains a significant matter of consequence. Methods: All patients who were surgically resected for branch-duct IPMNs between January 2004 and July 2010 at the University Clinic of Heidelberg were analyzed. Clinical characteristics of the patients and preoperative imaging were examined with regard to the size of the lesions, presence of mural nodules, thickening of the wall, dilation of the main pancreatic duct, and tumor markers. Results were correlated with histopathological features and were discussed with regard to the literature. Results: Among a total of 287 consecutively resected IPMNs, 123 branch-duct IPMNs were identified analyzing preoperative imaging. Some 69 branch-duct IPMNs were less than 3 cm in size, without mural nodules, thickening of the wall, or other features characteristic for malignancy (“Sendai negative”). Of all the Sendai negative branch-duct IPMNs, 24.6% (17/69) showed malignant features (invasive carcinoma or carcinoma in situ) upon histological examination of the surgical specimen. Conclusions: Although many branch-duct IPMNs are small and asymptomatic, they harbor a significant risk of malignancy. We believe that both main-duct and branch-duct IPMNs represent premalignant lesions. This should be taken into account for adequate therapeutic management. With regard to these results, the current Sendai criteria for branch-duct IPMNs need to be adjusted.